2002
DOI: 10.1081/fri-120014353
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Dihydrojasmonate and Its Stereoisomers: Sensory Properties and Enantioselective Analysis

Abstract: Enantiomeric methyl dihydrojasmonates (MDHJs) were separated by chiral gas chromatography (GC) and high performance liquid chromatography. Organoleptical evaluation clearly revealed that all four stereoisomers are odor-active and differ in their olfactory properties. Using enantio-multidimensional capillary GC -mass spectrometry with heptakis(2,3-di-O-methyl-6-O-tert butyldimethylsilyl)-b-cyclodextrin as the chiral stationary phase, the direct enantioselective analysis of all four stereoisomers of MDHJ in nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 30 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Whereas methyl dihydrojasmonate has been identified in several natural sources, 182 its presence as a trace element in JA has been cited only once but never confirmed on the grounds of reliable evidence. 136,149 On one occasion only, this author has detected traces of methyl (E)-dihydrojasmonate in JA from Grasse, but without being able to rule out any possible exogenous contamination.…”
Section: Methyl Jasmonatementioning
confidence: 99%
See 1 more Smart Citation
“…Whereas methyl dihydrojasmonate has been identified in several natural sources, 182 its presence as a trace element in JA has been cited only once but never confirmed on the grounds of reliable evidence. 136,149 On one occasion only, this author has detected traces of methyl (E)-dihydrojasmonate in JA from Grasse, but without being able to rule out any possible exogenous contamination.…”
Section: Methyl Jasmonatementioning
confidence: 99%
“…Another route to methyl jasmonate involves artificial photo‐oxidation of polyunsaturated C18 acid (as methyl ester), 181 but it is not expected to occur significantly at any stage of JA processing. Whereas methyl dihydrojasmonate has been identified in several natural sources, 182 its presence as a trace element in JA has been cited only once but never confirmed on the grounds of reliable evidence 136,149 . On one occasion only, this author has detected traces of methyl ( E )‐dihydrojasmonate in JA from Grasse, but without being able to rule out any possible exogenous contamination.…”
Section: Jasmine Flowers Analysismentioning
confidence: 99%
“…The olfactory properties of over 1348 enantiomers have been reported since Rienäcker and Ohloff published the first data regarding the enantioselective perception of β ‐citronellol in 1961 . Many studies have shown that stereostructure of odorants greatly affects the odour properties either in terms of feature or odour intensity …”
Section: Introductionmentioning
confidence: 99%
“…Currently, 2 is a highly prized fragrance ingredient for the manufacture of high grade perfumes and also finds utility in fruit flavors, tea, tobacco, and laundry products. 1,4 …”
Section: Introductionmentioning
confidence: 99%